PERANCANGAN SISTEM PENGOLAHAN DATA KUTIPAN AKTA NIKAH (KAN) PADA KANTOR URUSAN AGAMA ( KUA ) PADANG PANJANG BARAT BERBASIS PEMOGRAMAN PHP - Eva Yulianti; Fitri Yanti (Jurnal Teknoif Teknik Informatika Institut Teknologi Padang, 2014)
Administration the office of religious affairs (KUA) west Padang Panjang is responsible for data processing citations marriage certificate (KAN). KUA west Padang Panjang yet provide a good system in data processing KAN. KAN data processing itself is an important, to facilitate the matter, made of a data processing system KAN. This research aims to build a system that can simplify KAN KUA to process data relating to the marriage certificate data, quotes and deed. system is built with PHP programming using MySQL database and Apache web servers. This system will facilitate the west Padang Panjang KUA to produce more rapid and complete data processing KAN.